Management of lipedema with a biphasic ketogenic/low-carbohydrate diet: a case report - Cannataro, Roberto; Abrego-Guandique, Diana Marisol; Cione, Erika (Frontiers in Nutrition, 2026)
Lipedema is a multifactorial disorder with a negative evolutionary trend, influenced by genetic, hormonal, metabolic, and vascular factors that are not fully understood. Inflammation is a typical feature of lipedema and can be managed by limiting glycemic spikes. Herein, we report the case of a patient diagnosed with lipedema who followed a ketogenic diet (KD) for 6 months, resulting in a weight loss of 12 kg. Afterward, she transitioned to a low-carbohydrate (LC) diet for an additional 6 months, maintaining the good results achieved in terms of quality of life (QoL) improvement, weight control, and pain management. The patient regularly engaged in resistance training, which preserved and improved muscle mass. The primary and new outcome was due to the introduction of the second phase of the nutritional plan, specifically the low-carbohydrate diet, which could be an innovative approach. Often, diets that contain standard amounts of carbohydrates do not yield appreciable results.